Dilemma and implication of COVID-19 recurrences among healthcare workers - Shah, Anuradha Kunal; Velhal, Gajanan D.; Raul, Mayuri Umesh (International Journal Of Community Medicine And Public Health, 2021)
Reports of second infections with COVID-19 have intrigued researchers around the globe. They increase the burden on the already surging infected cases and add to the existing stigma around COVID. Moreover, it is mentally and physically taxing for the individual to go through the same stress for the second time. We aim to describe three cases of Re-Detected Positives (RDP) among healthcare workers in a tertiary care institute. The case histories were taken in detail over the telephone comparing the course, clinical history, contact history, and lab investigations of a first and second infection in each of them. A standard format developed for contact tracing in the institute was used for this. The period observed between two infections in these cases were 2-3 months and all the cases had tested negative by RTPCR before re-testing positive. Case 1: RDP by RTPCR 2.5 months after the first episode. He was asymptomatic, anti-bodies to SARS-Co-V 2 were also present in serum. Case 2 and 3: RDP by RTPCR and rapid antigen around 2.5 months after the first episode. They were symptomatic, antibodies absent and the contacts subsequently turned positive. Prolonged shedding of virus, reactivation, reinfection, dead viral shedding, false test results is the possible causes scientifically discussed. Second infections can be seen in COVID-19. It is expected to present with more severe signs and symptoms. Hence, general precautions should be taken even after recovery from the disease, especially in the case of HCWs who are constantly exposed.